Coherent Cherenkov radiation as an intense THz source. (July 2016) - Bleko, V; Karataev, P; Konkov, A; Kruchinin, K; Naumenko, G; Potylitsyn, A; Vaughan, T
Abstract: Diffraction and Cherenkov radiation of relativistic electrons from a dielectric target has been proposed as mechanism for production of intense terahertz (THz) radiation. The use of an extremely short high-energy electron beam of a 4th generation light source (X-ray free electron laser) appears to be very promising. A moderate power from the electron beam can be extracted and converted into THz radiation with nearly zero absorption losses. The initial experiment on THz observation will be performed at CLARA/VELA FEL test facility in the UK to demonstrate the principle to a wider community and to develop the radiator prototype. In this paper, we present our theoretical predictions (based on the approach of polarization currents), which provides the basis for interpreting the future experimental measurements. We will also present our hardware design and discuss a plan of the future experiment.